A FIGURATIVE LANGUAGE ANALYSIS AND FREQUENCY USED OF MELLY GOESLAW’S MASTERPIECES IN SOUNDTRACK DRAMA - Henny Uswatun Hasanah (OKARA: Jurnal Bahasa dan Sastra, 2013)
Who don’t know about Melly Goeslaw? There are many things that she does, such as to be a singer, to be songwriter for other people, to be a singer who feat/duet with other people, or to be songwriter for romantic drama that makes her to be famous with a nickname “the Queen of Soundtrack”. She has a lot of songs that is so phenomenal by beautiful words and smooth tone music which makes the listeners to be happiness and like the music so much. There are many songs that use figurative languages which contains the meaningful message from every song from 1990s until 2013. Then, it gives motivation and inspiration by her stylistically in romantic or beautiful words for all of audience who listen it.